2013
DOI: 10.1089/dia.2013.0008
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Eating Behaviors in Youth with Type 1 Diabetes: Prospective Pilot Assessment Following Initiation of Insulin Pump Therapy

Abstract: Background: There is risk for disordered eating behaviors in type 1 diabetes, especially related to insulin manipulation. Implementation of insulin pump therapy may encourage either normalization of eating behaviors or a greater focus on food intake due to renewed emphasis on carbohydrate counting. There is need for prospective studies to assess disordered eating behaviors upon implementation of pump therapy using diabetes-specific measurement tools. Subjects and Methods: In a multicenter pilot study, 43 youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 14 publications
1
28
0
3
Order By: Relevance
“…Our findings confirm recent studies that have reported associations between more disordered eating behaviours and female sex , higher BMI and poorer glycaemic control in people with Type 1 diabetes. In a recent large epidemiological study of 52 215 children and young adults with Type 1 diabetes, 467 individuals had an eating disorder according to the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders criteria .…”
Section: Discussionsupporting
confidence: 92%
“…Our findings confirm recent studies that have reported associations between more disordered eating behaviours and female sex , higher BMI and poorer glycaemic control in people with Type 1 diabetes. In a recent large epidemiological study of 52 215 children and young adults with Type 1 diabetes, 467 individuals had an eating disorder according to the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders criteria .…”
Section: Discussionsupporting
confidence: 92%
“…Finally, innovations in diabetes technology, such as continuous glucose monitoring (CGM) and insulin pumps (CSII), can have a relevant impact on eating behaviors [ 60 ]. Theoretically, they can have opposite effects.…”
Section: Interventions For Prevention and Treatmentmentioning
confidence: 99%
“…However, the use of modern technologies is associated with a significant decrease in insulin doses needed to maintain normal glucose levels. In a recent study carried out in adolescent with T1D, it was evidenced that use of CSII was associated with diminished endorsement of disordered eating behavior [ 60 ]. However, further studies are needed to evaluate the true impact of CGM and CSII on eating problems of T1D patients.…”
Section: Interventions For Prevention and Treatmentmentioning
confidence: 99%
“…15,27 A recent study demonstrated that DEB decreased over 6 months in a sample of youth who had transitioned to an insulin pump suggesting that the insulin pump may help mitigate DEB and normalize eating patterns. 15 Our findings suggest the importance of screening for DEB in youth with T1D, particularly during this transition from MDI regimens to an insulin pump. This period of time after the individual has been living with the illness and managing using an MDI regimen appears to be a time of risk for DEB, particularly with a higher BMI, and concurrent depressive symptoms and emotion dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 T1D youth who are newly transitioning to pump therapy may have had the experience of unsuccessful regulation of blood glucose with insulin injections, which increases hypoglycemia. 15 Thus, it is reasonable to expect that youth living with T1D prior to transition to insulin pump may demonstrate increased emotion dysregulation, which in turn is associated with increased risk for DEB.…”
mentioning
confidence: 99%